Simbiosis Mutualisme Badan Publik Dan Pengendali Data Pribadi Terhadap Perlindungan Hukum Kebocoran Atas Privasi Dan Data Pribadi - Kesuma, Derry Angling (Sekolah Tinggi Ilmu Hukum Sumpah Pemuda, 2024)
Social life requires personal data. The cybersecurity sector also covers the protection of personal data, which is the responsibility of related agencies such as the Police, BSSN, BIN, and the Ministry of Defence. Criminal responsibility for the data leak should not release anyone who did it, including the administrator of the darknet site that turned into a black market. Under the Personal Data Protection Act, individuals, including those who run a business or purchase online at home, can be considered as controllers of personal data. Thus, these individuals are legally fully responsible for the processing of their personal data. Government is the executive, legislative, judicial, and other bodies related to state operations, called public bodies. A public body may be the controller or processor of personal data, and is required by Articles 20 to 50 of the Personal Data Protection Act. Among other things, they are required to provide proof of the consent of the personal data subject when carrying out the processing of personal data, and to provide other proof that indicates consent to the data subject.